Bibliometric and visual analysis of SGLT2 inhibitors in cardiovascular diseases - Pan, Runfang; He, Yuqing; Melisandre, Wan; Zhang, Yunyi; Su, Wenyuan; Feng, Jiaming; Jia, Chengyao; Li, Shaoling; Liu, Baonian (Frontiers in Pharmacology, 2024)
Background: Cardiovascular diseases (CVD) pose a significant threat to human health due to their high mortality and morbidity rates. Despite advances in treatments, the prevalence and impact of cardiovascular disease continue to increase. Sodium-glucose transporter 2 inhibitors (SGLT2i), initially approved for the treatment of type 2 diabetes, have important research value and promising applications in reducing CVD risk, especially in heart failure (HF) and atherosclerosis patients with cardiovascular disease (ASCVD). This study aims to comprehensively review the latest progress, research trends, cutting-edge hot spots, and future development directions of SGLT2i in the field of CVD through bibliometric analysis.Methods: Articles related to MSCs in cardiovascular diseases were sourced from the Web of Science. The bibliometric analysis was conducted using CiteSpace and VOSviewer, and a knowledge map was created based on the data obtained from the retrieved articles.In this article, we screened 3,476 relevant studies, including 2,293 articles and 1,183 reviews. The analysis found that the number of papers related to the application of SGLT2i in CVD has generally increased, peaking in 2022. The United States and China contributed the largest number of papers, with the United States accounting for 36.97% of the total and also ranking first in terms of the number of citations. However, China's high-quality papers are slightly lacking and need further improvement.Keyword analysis showed that empagliflozin, dapagliflozin, diabetes, and heart failure were the most common terms, reflecting the main research interests in currently published papers in this field.: Bibliometric analysis showed a robust and growing interest in the application of SGLT2i for treating CVD. By summarizing the latest progress of SGLT2i in the field of CVD, exploring research hotspots, and looking forward to future research development trends, this article provides valuable insights for thinking about research prospects.